Specialization in Europe and asymmetric shocks: Potential risks of EMU - Raúl Ramos; Miquel Clar; Jordi Suri\~nach (European Regional Science Association (ERSA), 1998)
One of the most obvious consequences of a monetary union is that monetary policy is lost as an instrument of national macroeconomic policy. The loss of the exchange rate as a national policy instrument has important implications for macroeconomic stability in the presence of asymmetric shocks, unexpected shocks that do not affect every nation in an equal way. The empirical literature on Optimum Currency Areas has concluded that the probability of asymmetric shocks to occur at a national level has tended to diminish in the Economic and Monetary Union (EMU) as a result of the intensification of the integration process during the most recent years. Therefore, since Economic Geography Theories predict an increasing specialisation of regions as a result of reallocation of industrial activity, the degree of asymmetry of industry-specific shocks will be specially relevant to determine if benefits overweight the costs associated to EMU. Previous studies, such as Bayoumi and Eichengreen (1995), Helg et al. (1995) or Ghosh and Wolf (1997), have examined to what extent sectoral asymmetric shocks have been relevant in the past using, mainly, static measures of asymmetries such as the correlation coefficients between series of sectoral shocks previously calculated from VAR or sVAR models (Blanchard and Quah, 1989; Blanchard and Katz, 1992). In this paper, we study the evolution of industry-specific asymmetries in Europe from a dynamic point of view (applying the methodology proposed by Boone, 1997) in order to obtain new evidence about the potential risks of EMU in the scenario proposed by Economic Geography Theories.
Keywords: 330